Do meteoritic silicon carbide grains originate from asymptotic giant branch stars of super-solar metallicity?. (15th January 2018) - Lugaro, Maria; Karakas, Amanda I.; Pető, Mária; Plachy, Emese
Abstract: We compare literature data for the isotopic ratios of Zr, Sr, and Ba from analysis of single meteoritic stardust silicon carbide (SiC) grains to new predictions for the slow neutron-capture process (the s process) in metal-rich asymptotic giant branch (AGB) stars. The models have initial metallicities Z = 0.014 (solar) and Z = 0.03 (twice-solar) and initial masses 2–4.5 M ⊙, selected such as the condition C/O > 1 for the formation of SiC is achieved. Because of the higher Fe abundance, the twice-solar metallicity models result in a lower number of total free neutrons released by the 13 C( α, n) 16 O neutron source. Furthermore, the highest-mass (4–4.5 M ⊙ ) AGB stars of twice-solar metallicity present a milder activation of the 22 Ne( α, n) 25 Mg neutron source than their solar metallicity counterparts, due to cooler temperatures resulting from the effect of higher opacities. They also have a lower amount of the 13 C neutron source than the lower-mass models, following their smaller He-rich region. The combination of these different effects allows our AGB models of twice-solar metallicity to provide a match to the SiC data without the need to consider large variations in the features of the 13 C neutron source nor neutron-capture processes different from the s process. This raises the question if the AGB parent stars of meteoritic SiC grains were in fact on average of twice-solar metallicity. The heavier-than-solar Si and Ti isotopic ratios in the same grains are in qualitative agreement with an origin in stars of super-solar metallicity because of the chemical evolution of the Galaxy. Further, the SiC dust mass ejected from C-rich AGB stars is predicted to significantly increase with increasing the metallicity.